Model Bimbingan Belajar Behavioristik dan Pandangannya dalam Perspektif Islam - Ningsih Fadhilah (Jurnal Hikmatuna, 2016)
Behavioristic theory emphasizes on shaping observable behaviors as the result of the learning process. Learning is about changing the behavior as the result of interaction between stimulus and responses. One can be considered to have learned when he is able to show changing behaviors. The behavioristic learning model is applied by considering the Thomdike’s primary laws: law of readiness, law of exercise, andlaw of effect and five subsidiary laws/ minor laws)i.e.Law of multiple response, Law of attitude (law of set, law of disposition), Law of partial activity (law of prepotency element), Law of response by analogy (law of assimilation), Law of associative shifting. On their application, behavioristic learning strategies cannot be separated from the behavioural principles, including: (1) Reinforcement and Punishment; (2) Primary and Secondary Reinforcement; (3) Schedules of Reinforcement; (4) Contingency Management; (5) Stimulus Control in Operant Learning; (6) The Elimination of Responses. In Islam, the influential factors toward childreninclude not only the environmental conditioning, but also heredity. Besides, there is also one the most important thing above all: God’s will or iradah, approval and blessing. These tauhid principles are the distinguishing factors between Islamic education and behavioristic theory.